The Study of Living Hadith of the Ancak Tradition in Wedoroklurak Village, Candi, Sidoarjo - Umi Hanik; Ibnu Hajar Ansori (UIN Sunan Kalijaga Yogyakarta, 2019)
This article is a study of the Ancak tradition in the Wedoroklurak village community of Candi District in Sidoarjo. The study conducted with the theory of Living Hadith. The results of the study concluded that the Ancak Tradition is an activity that arises out of gratitude to God for agricultural products harvested by the community. The thanks were then expressed in the form of alms-giving and sending prayers to the village’s founding figures. The activity was carried out at the grave of Mbah Nursinah Kik Graji Kendil Wesi as the leader of the six figures who opened the village at that time. The series of events began with Khatmil Qur’an, followed by spiritual sparks, prayers, and shared meals. Seeing from the perspective of the Hadith, motivational aspects supported by the Hadith associated with alms from the results of efforts, as narrated by al-Darimi, al- Nasa’i, Muslims, al-Tirmidhi, Ibn Majah and al-Bukhari. From the form of its activities, the Ancak tradition can return to the general nature of the propositions relating to the virtue of reading the Qur’an, graves pilgrimage, praying for ancestors, and blessings to eat together. Judging from the series of traditional activities, it seems that nothing violates religious law, so the claims of local people who call Ancak as a religious tradition can be accepted. Its sustainability needs to be maintained and preserved as local wisdom that can foster harmony and the spirit of cooperation, also to instill the value of religiosity that is rooted in society, especially the value of gratitude and alms-giving.[Artikel ini adalah studi tentang tradisi Ancak di komunitas desa Wedoroklurak, Kabupaten Candi, Sidoarjo. Penelitian dilakukan melalui perspektif Living Hadith. Hasil penelitian menyimpulkan bahwa Tradisi Ancak adalah kegiatan yang muncul sebagai rasa terima kasih kepada Tuhan untuk produk pertanian yang dipanen oleh masyarakat. Rasa terima kasih kemudian diungkapkan dalam bentuk pemberian sedekah dan mengirimkan doa kepada para tokoh pendiri desa. Kegiatan tersebut dilakukan di makam Mbah Nursinah Kik Graji Kendil Wesi sebagai pemimpin dari enam tokoh yang membuka desa pada saat itu. Rangkaian acara dimulai dengan Khatmil Qur'an, diikuti oleh siraman rohani, doa, dan makan bersama. Dilihat dari perspektif Hadis, aspek motivasi didukung oleh Hadis terkait dengan sedekah dari hasil usaha, seperti yang diriwayatkan oleh al-Darimi, al- Nasa'i, Muslim, al-Tirmidzi, Ibn Majah dan al-Bukhari. Dari bentuk kegiatannya, tradisi Ancak dapat dikembalikan kepada karakteristik umum yang berkaitan dengan keutamaan membaca Al-Qur'an, ziarah kuburan, berdoa untuk leluhur, dan berkah untuk makan bersama. Menilik dari rangkaian kegiatan tradisionalnya, tampaknya tidak ada yang sesuatu yang terlihat melanggar hukum agama, sehingga klaim masyarakat setempat yang menyebut Ancak sebagai tradisi agama dapat diterima. Keberlanjutannya perlu dipertahankan dan dilestarikan sebagai kearifan lokal yang dapat menumbuhkan kerukunan dan semangat kerja sama, juga menanamkan nilai relijius yang mengakar dalam masyarakat, terutama nilai syukur dan pemberian sedekah.]